Who is utilizing anti-retroviral therapy in Ghana: An analysis of ART service utilization - Dako-Gyeke Phyllis; Snow Rachel; Yawson Alfred E (BMC, 2012)
Abstract Introduction The global scale-up of antiretroviral therapy (ART) for HIV patients has led to concerns regarding inequities in utilization of ART services in resource-limited contexts. In this paper, we describe regional and sex differentials in the distribution of ART among adult HIV patients in Ghana. We highlight the need for interventions to address the gender-based and geographic inequities related to the utilization of ART services in Ghana. Methods We reviewed National AIDS/STIs Control Program's ART service provision records from January 2003 through December 2010, extracting data on adults aged 15+ who initiated ART in Ghana over a period of eight years. Data on the number of patients on treatment, year of enrollment, sex, and region were obtained and compared. Results The number of HIV patients receiving ART in Ghana increased more than 200-fold from 197 in 2003, to over 45,000 in 2010. However, for each of six continuous years (2005-2010) males comprised approximately one-third of adults newly enrolled on ART. As ART coverage has expanded in Ghana, the proportion of males receiving ART declined from 41.7% in 2004 to 30.1% in 2008 and to 27.6% in 2010. Also, there is disproportionate regional ART utilization across the country. Some regions report ART enrollment lower than their percent share of number of HIV infected persons in the country. Conclusions Attention to the comparatively fewer males initiating ART, as well as disproportionate regional ART utilization is urgently needed. All forms of gender-based inequities in relation to HIV care must be addressed in order for Ghana to realize successful outcomes at the population level. Policy makers in Ghana and elsewhere need to understand how gender-based health inequities in relation to HIV care affect both men and women and begin to design appropriate interventions.